The Indian government and justice apparatus from the Ovandine reforms - Diego-Fernández Sotelo, Rafael (2008)
There are three constitutive moments of the Indian government from the end of the 15th to the 16th century. In the first instance, under the tutelage of the Catholic Monarchs, the political pillars of the Indian building are solidly established based on the papal bulls, the international treaties between Castile and Portugal, and the capitulations of discovery, conquest and colonization; In a second stage, with the creation of the Council of the Indies by Carlos V, in 1524, most of the Indian Royal Courts were founded, which would be the basis of the political-territorial division of the New World; Finally, Felipe II entrusted Juan de Ovando with the visit to the Council of the Indies in 1568, which he would then preside over between 1571 and 1575, when the Indian government apparatus was completed and would remain until the duo of Carlos III and José de Gálvez introduce the so-called Bourbon reforms.